Transcriptomic approach predicts a major role for transforming growth factor beta type 1 pathway in L‐Dopa‐induced dyskinesia in parkinsonian rats. (11th September 2020) - Dyavar, Shetty Ravi; Potts, Lisa F.; Beck, Goichi; Dyavar Shetty, Bhagya Laxmi; Lawson, Benton; Podany, Anthony T.; Fletcher, Courtney V.; Amara, Rama Rao; Papa, Stella M.
Abstract: Dyskinesia induced by long‐term L‐Dopa (LID) therapy in Parkinson disease is associated with altered striatal function whose molecular bases remain unclear. Here, a transcriptomic approach was applied for comprehensive analysis of distinctively regulated genes in striatal tissue, their specific pathways, and functional‐ and disease‐associated networks in a rodent model of LID. This approach has identified transforming growth factor beta type 1 (TGFβ1) as a highly upregulated gene in dyskinetic animals. TGFβ1 pathway is a top aberrantly regulated pathway in the striatum following LID development based on differentially expressed genes (> 1.5 fold change and P < 0.05). The induction of TGFβ1 pathway specific genes, TGFβ1, INHBA, AMHR2 and PMEPA1 was also associated with regulation of NPTX2, PDP1, SCG2, SYNPR, TAC1, TH, TNNT1 genes. Transcriptional network and upstream regulator analyses have identified AKT‐centered functional and ERK‐centered disease networks revealing the association of TGFβ1, IL‐1β and TNFα with LID development. Therefore, results support that TGFβ1 pathway is a major contributor to the pathogenic mechanisms of LID. Abstract : Transcriptomic approach predicted a major role for transforming growth factor β type 1 pathway in L‐Dopa‐induced dyskinesia. Transforming growth factor β type 1 pathway was identified as a top regulatory biological pathway in the striatum of L‐Dopa‐treated rats compared to controls using pathway enrichment in IPA software based on the list of differentially expressed genes (>1.5 fold change and < 0.05 p value).